THE EFFECT OF WORK ETHIC, POSITION MUTATION, AND JOB SATISFACTION ON LECTURER PERFORMANCE WITHIN THE FACULTY OF ECONOMICS AND ISLAMIC BUSINESS UIN ALAUDDIN MAKASSAR - Gani, Nuraeni; Suwandi, Memen (Assets : Jurnal Ekonomi, Manajemen dan Akuntansi, 2024)
This study aims to analyze the effect of work ethic, job transfer, and job satisfaction on lecturer performance at the Faculty of Economics and Islamic Business, State Islamic University of Alauddin Makassar. The background of this research is the importance of these factors in improving the performance of lecturers in the academic environment. The research was conducted using purposive sampling method, with a sample size of 55 lecturers. Data were collected through questionnaires in accordance with the research objectives. Data analysis used multiple linear regression, T test, F test, and coefficient of determination (R2) test. The results showed that work ethic has a positive and significant effect on lecturer performance, job transfer has a positive and significant effect on lecturer performance, and job satisfaction has a positive and significant effect on lecturer performance within the Faculty of Economics and Islamic Business. In conclusion, work ethic, job transfer, and job satisfaction have an important role in improving the performance of lecturers at the Faculty of Economics and Islamic Business, State Islamic University of Alauddin Makassar. These research applied in Faculty of Islamic Economics and Business, Alauddin State Islamic University Makassar. The sample uses the purposive sampling, that is, sampling based on certain considerations or criteria. All samples of 55 respondents at Faculty of Islamic Economics and Business, Alauddin State Islamic University Makassar. A method of data used is live interview to the many involved in the problem under discussion and give a questionnaire for lecturer according to research conducted. . Data analysis was done using multiple linear regression analysis, test T test, test F test and The coefficient of determination (R2). The results of an analysis of shows that work ethic is a influenced to lecturer performance at Faculty of Islamic Economics and Business, Alauddin State Islamic University Makassar; job transfers is a influenced to lecturer performance at Faculty of Islamic Economics and Business, Alauddin State Islamic University Makassar; job satisfaction is a influenced to lecturer performance at Faculty of Islamic Economics and Business, Alauddin State Islamic University Makassar; and x01, job transfers and job satisfaction is a influenced to lecturer performance atFaculty of Islamic Economics and Business, Alauddin State Islamic University Makassar Keywords: Work ethic, Job transfers, Job satisfaction and Lecturer performance.